2019
DOI: 10.1016/j.jhep.2019.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-primed hepatocyte transplantation in murine monogeneic dyslipidemia normalizes cholesterol and prevents atherosclerosis

Abstract: Background & Aims: Inherited abnormalities in apolipoprotein E (ApoE) or low-density lipoprotein receptor (LDLR) function result in early onset cardiovascular disease and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Pharmacological and temporary induction of liver regeneration may, therefore, be a viable strategy to enhance hepatocyte gene repair in a clinical setting. In fact, T3 analogs with hepatocyte specificity have been used in rodents to induce liver regeneration 29 and are in clinical trials for hyperlipidemia in humans. 30 We also investigated whether the FA DNA repair pathway 31,32 plays a role in hepatocyte gene repair.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological and temporary induction of liver regeneration may, therefore, be a viable strategy to enhance hepatocyte gene repair in a clinical setting. In fact, T3 analogs with hepatocyte specificity have been used in rodents to induce liver regeneration 29 and are in clinical trials for hyperlipidemia in humans. 30 We also investigated whether the FA DNA repair pathway 31,32 plays a role in hepatocyte gene repair.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 15 Dyslipidemia is associated with an increased risk of the development of atherosclerosis. 25 Several studies have demonstrated that atherosclerosis promotes neuronal degeneration or neurotransmitter synthesis disorder, 26 , 27 which leads to a disorderly increase in lipid metabolites (such as oxidized lipids). The accumulation of oxidized lipids in the microvasculature stimulates the local release of inflammatory mediators, 28 which can directly initiate and accelerate sensitization of pain-sensing nociceptors located at functional afferent neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, irradiation of the host liver has been studied in both rats and humans showing some benefit regarding cell proliferation 45 . Even better results have been obtained by employing the combination of focal radiation with hepatic cell growth stimuli (hepatic mitogen GC-1) in mice 46 . Other approaches include gene therapy to provide a selected repopulating advantage to hepatocytes 47 or strategies to prevent immunological activation that would hamper engraftment 48 .…”
Section: Hepatocyte Transplantation (Ht) and Cell Therapiesmentioning
confidence: 99%